2011
DOI: 10.1002/ldr.1086
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable land management in the drylands: Scientific connections in monitoring and assessing dryland degradation, climate change and biodiversity

Abstract: The United Nations Convention to Combat Desertification and its sister conventions, the United Nations Framework Convention on Climate Change and the Convention on Biological Diversity, all aim to halt or mitigate the deterioration of the ecological processes on which life depends. Sustainable land management (SLM) is fundamental to achieving the goals of all three Conventions. Changes in land management undertaken to address dryland degradation and desertification can simultaneously reduce net greenhouse gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 79 publications
0
78
0
2
Order By: Relevance
“…All decisions that involve trade-offs involve valuation, whether implicitly or explicitly (Costanza et al, 1997(Costanza et al, , 2011b(Costanza et al, , 2014. Historically, most land degradation valuations have been focused on marketed physical goods such as food, feed, fibers and fuel production using commodity prices (Barbier, 2000;Cowie et al, 2011;ELD-Initiative, 2013;Nkonya et al, 2013). It is apparent now though, that a more comprehensive assessment of the full range of assets and services of the landscape is necessary to capture its real value for decision making (Costanza et al, 2013).…”
Section: Methods For Valuing Land Use and Managementmentioning
confidence: 98%
“…All decisions that involve trade-offs involve valuation, whether implicitly or explicitly (Costanza et al, 1997(Costanza et al, , 2011b(Costanza et al, , 2014. Historically, most land degradation valuations have been focused on marketed physical goods such as food, feed, fibers and fuel production using commodity prices (Barbier, 2000;Cowie et al, 2011;ELD-Initiative, 2013;Nkonya et al, 2013). It is apparent now though, that a more comprehensive assessment of the full range of assets and services of the landscape is necessary to capture its real value for decision making (Costanza et al, 2013).…”
Section: Methods For Valuing Land Use and Managementmentioning
confidence: 98%
“…Our research indicated that in water resource-limited ecosystems, although change of land use has the potential to create higher economic return, it may simultaneously incur ecological risks on watershed health and carbon cycling in both local and nearby systems. Once these ecosystems have been negatively impacted, a sustainable land management plan made with full consideration of human-environment interactions and socioeconomic drivers should be adopted to help the recovery of the disturbed ecosystem (Cowie et al 2011;Eppink et al 2012;Nkonya et al 2011;Schwilch et al 2011), despite the fact that some of the ecosystem services may be permanently lost (Benayas et al 2009). Therefore, management of integrated watersheds should put water resources as the central consideration, as water is a basic resource that constrains many other socio-ecological systems.…”
Section: Land Use Management Toward Sustainability In Drylandsmentioning
confidence: 99%
“…Due to the arid climate (low precipitation and high evaporative potential), the ecosystems in semi-arid areas are particularly vulnerable to human disturbances (Cowie et al 2011) and are limited when providing water-based ecosystem services such as water supplies to people. Because of climate change, human activities, steep terrains, and sparse vegetation (Su et al 2012) in the semi-arid areas of the Loess Plateau, serious soil erosion has occurred.…”
Section: Introductionmentioning
confidence: 99%